Fostering Investment Efficiency in Indonesian Firms: Empirical Evidence and Recommendations for Future Research - Risdiawan, Hanafi; Aryani, Y Anni; Setiawan, Doddy; Sudaryono, Eko Arief (Journal of Accounting Research, Organization and Economics, 2024)
Objective The purpose of this research is to review and examine the empirical evidence on investment efficiency in Indonesia.Design/methodology This research employs bibliographic analysis. This research utilizes 30 articles published between 2015 and 2023 in internationally recognized Scopus journals and nationally recognized Sinta 2 journals.Results This research identifies three categories of factors that impact investment efficiency namely financial, governance, and non-financial factors. Financial factors are essential in assessing investment effectiveness, while corporate governance factors can enhance a firm's investment decisions. Non-financial factors related to managerial personnel can also significantly impact a firm's investment efficiency. Future research on investment efficiency in Indonesia should incorporate diverse variables and external factors, conduct comparative studies with neighboring countries, and collaborate with industry stakeholders to bridge the gap between theory and practice.Research limitations/implications This research focuses primarily on analyzing the literature on investment efficiency in Indonesia by using charting the field method. This research adds to the literature on the various factors that affect the investment efficiency of firms.Novelty/Originality This research is the first to conduct a comprehensive literature review on investment efficiency in Indonesia. By systematically analyzing findings from various studies, this research offers a unique and thorough understanding of investment efficiency within the Indonesian context.